The Philosopher In The Newspaper: Serhiy Krymsky As A Public Intellectual - Melnyk, Andriy (Social Communication, 2015)
Abstract Interactions of philosophical and journalistic spheres, mediatization of philosophy are main problems of this article. Author considers public philosophy of contemporary Ukrainian philosopher Serhiy Krymsky and determines a role of philosophical journalism in modern media discourse.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9zYy0yMDE1LTAwMDM